First Russian Interdisciplinary Study to Approach Socio-Humanitarian Issues of Organ Donation. (August 2017) - Reznik, Oleg; Skvortsov, Andrey; Reznik, Aleksandr; Popova, Olga; Tishchenko, Pavel
Abstract : The thesis has been prepared with the financial support of the Russian Science Foundation, Grant No. 17-18-01444 of 2017 year. The innovation process in its essence is a mix of knowledge production, discoveries and technological inventions in conjunction with the creation of a favorable social environment for the positive perception of scientific achievements, their uptake, public support and successful implementation in practice. Existing difficulties in the progress of national organ donation and transplantation programs as a form of high-tech innovative research and clinical field to some extent are related to the insufficient theoretical understanding of emerging social, humanitarian and other problems. We introduce First supported by the Russian State integrated interdisciplinary study of these problems started as a cooperation of doctors, philosophers and theologians. Interdisciplinary team will conduct adequate research, based on current scientific knowledge and socio-humanitarian innovation policy including modern socio-humanitarian assessment. Particularly, the philosophical, religious, moral and anthropological problems of commodification (including commercialization) of the human body and its organs will be explored in order to analyze the moral paradoxes of development of transplantation and organ donation as a kind of high-tech innovative technologies. Project results will have essential value in respect of deepening of theoretical (philosophical, religious, anthropological, medical) interpretation of a human body as a gift, a resource, and a property. On specific material of technologies of organ donation essentially important aspects of interaction of innovative science and society will be presented, crucial importance of procedures of co-production of scientific knowledge and technologies with production of social values, normative ethical and legal systems will be described and interpreted. Creation of methodological framework for assessment of bioethical risks in transplantology and organ donation, development of the systems of media support and diagnostics of public perception of transplantology will be essential for the future of innovation programs and will make an essential contribution to development of domestic organ donorship. The research of ethical, social and legal problems of organ transplantation will be helpful for promotion of trust between innovative medicine and citizens that could results in betterment of healthcare in this area.